Improving Grade VII Students’ Achievement in Procedure Text Through Still Pictures - Berta Ito Lubis; Tina Mariany Arifin (Universitas Negeri Medan, 2014)
ABSTRACT This study was conducted as an attempt to improve students’ writing achievement in a procedure text by using Still Pictures. The method of the study was Classroom Action Research with two cycles and six meetings. The subject of the study was the students of Grade VII students’ MTs. S. Syahbuddin Mustafa Nauli. The research was conducted in two cycles and each cycle consists of three meetings. The instruments for collecting data were taken from writing tests as quantitative data. The result shows the improvement of the students’ score from orientation test to Cycles I and II tests. The mean of the students’ score for orientation test as Test I was 50.41, Cycle I test was 66.25, and Cycle II test was 85.41. The total percentage of the improvement from Orientation test to Cycles I and II tests was 99.2 %. It can be concluded that the use of Still Pictures improves students’ achievement in writing a procedure text. The qualitative data taken from Observation Sheet and Diary Notes show that the students’ were enthusiastic and attracted in writing a procedure text because the Still Pictures encourage their creativities and ideas to write better. For English teachers, it is suggested to use Still Pictures as one alternative media of teaching writing a procedure text.